2012
DOI: 10.4103/0971-6866.100764
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic abnormalities in 222 infertile men with azoospermia and oligospermia in Iran: Report and review

Abstract: BACKGROUND:Infertility affects approximately 10%-15% of couples in reproductive age. In half of the couples, causes are male-related, associated with impaired spermatogenesis. There is a complex correlation between genetics and infertility. Several factors affect on gametogenesis, from which factors that lead to chromosomal abnormalities are one of the best known. The aim of this study was to determine type and rate of chromosomal abnormalities in infertile azoospermic and oligospermic males in Iranian populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
10
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 33 publications
4
10
1
Order By: Relevance
“…Studies have reported variable frequency of major chromosomal alterations in patients with male infertility. In our present study, chromosomal alterations in the NOA men were 14.3%, which was higher than published data of the average level (8.2%) and the Indian average level (10.8%) (Akbari, Behjati, Pourmand, Asbagh, & Kachoui, ; Rao et al., ), and were lower than that in some Western countries (14.5%–26.3%) (Akbari et al., ; Akin, Onay, Turker, & Ozkinay, ; Frouzandeh, Saeideh, & Sanaz, ; Kate, Pokale, Jadhav, & Gangane, ; Mohammed et al., ; Rao et al., ). Such variability among different series is likely to be related to a dissimilar composition of the studied populations, mostly to the severity of male factor (Pylyp, Spinenko, Verhoglyad, & Zukin, ).…”
Section: Discussioncontrasting
confidence: 81%
“…Studies have reported variable frequency of major chromosomal alterations in patients with male infertility. In our present study, chromosomal alterations in the NOA men were 14.3%, which was higher than published data of the average level (8.2%) and the Indian average level (10.8%) (Akbari, Behjati, Pourmand, Asbagh, & Kachoui, ; Rao et al., ), and were lower than that in some Western countries (14.5%–26.3%) (Akbari et al., ; Akin, Onay, Turker, & Ozkinay, ; Frouzandeh, Saeideh, & Sanaz, ; Kate, Pokale, Jadhav, & Gangane, ; Mohammed et al., ; Rao et al., ). Such variability among different series is likely to be related to a dissimilar composition of the studied populations, mostly to the severity of male factor (Pylyp, Spinenko, Verhoglyad, & Zukin, ).…”
Section: Discussioncontrasting
confidence: 81%
“…The cause of spermatogenic failure in carriers of an X-autosome translocations is unknown, although spermatogenesis sperm production displays greater much more sensitivitye to disruption of meiosis disruption than oogenesis, owing to a number of meiotic cell-cycle checkpoints (Akbari et al, 2012). In this study, a carrier of one such translocation, 46,Y,t(X;9)(q13;q13.1), demonstrated oligozoospermia.…”
Section: Discussionmentioning
confidence: 63%
“…Significantly increased incidence of spermatozoa with defects in chromatin integrity and condensation, such as aneuploidy of chromosomes not involved in the translocation, and diploidy, were also found in translocation carriers exhibiting abnormal semen parameters. Moreover, normospermic men with reciprocal translocations carriers showed an increase in chromosome 13 disomy compared to control subjects (Akbari et al, 2012).…”
Section: Discussionmentioning
confidence: 89%
“…It is worth mentioning that in most of the countries, where benzene is being monitored poorly, non communicable disease like diabetes, cancer, human infertility, neurological disease, birth defects and cardiovascular problems are commonly widespread, however there are difference in the prevalence rate from country to country and urban and rural areas (Shaw et al, 2010, Ramachandran et al, 2010, Ghaffar et al, 2004, Lawes et al, 2008, Kearney et al, 2005, Goyal and Yusuf, 2006, Ferri et al, 2005, Akbari et al, 2012, Yasseen et al, 2001, Evens, 2004, Durkin, 2002, Motlagh et al, 2009, Ombelet et al, 2008, W.H.O., 2011. Diabetes, lungs and breast cancers are the most common diseases of India, Bangladesh, Pakistan, Iran, Egypt, Saudi Arabia, UAE, Malaysia and Indonesia.…”
Section: Discussionmentioning
confidence: 99%